Innovations and changes in the ICD‐11 classification of mental, behavioural and neurodevelopmental disorders - Reed, Geoffrey M.; First, Michael B.; Kogan, Cary S.; Hyman, Steven E.; Gureje, Oye; Gaebel, Wolfgang; Maj, Mario; Stein, Dan J.; Maercker, Andreas; Tyrer, Peter; Claudino, Angelica; Garralda, Elena; et al. (World psychiatry, 2019)
Following approval of the ICD‐11 by the World Health Assembly in May 2019, World Health Organization (WHO) member states will transition from the ICD‐10 to the ICD‐11, with reporting of health statistics based on the new system to begin on January 1, 2022. The WHO Department of Mental Health and Substance Abuse will publish Clinical Descriptions and Diagnostic Guidelines (CDDG) for ICD‐11 Mental, Behavioural and Neurodevelopmental Disorders following ICD‐11’s approval. The development of the ICD‐11 CDDG over the past decade, based on the principles of clinical utility and global applicability, has been the most broadly international, multilingual, multidisciplinary and participative revision process ever implemented for a classification of mental disorders. Innovations in the ICD‐11 include the provision of consistent and systematically characterized information, the adoption of a lifespan approach, and culture‐related guidance for each disorder. Dimensional approaches have been incorporated into the classification, particularly for personality disorders and primary psychotic disorders, in ways that are consistent with current evidence, are more compatible with recovery‐based approaches, eliminate artificial comorbidity, and more effectively capture changes over time. Here we describe major changes to the structure of the ICD‐11 classification of mental disorders as compared to the ICD‐10, and the development of two new ICD‐11 chapters relevant to mental health practice. We illustrate a set of new categories that have been added to the ICD‐11 and present the rationale for their inclusion. Finally, we provide a description of the important changes that have been made in each ICD‐11 disorder grouping. This information is intended to be useful for both clinicians and researchers in orienting themselves to the ICD‐11 and in preparing for implementation in their own professional contexts.